Perfil audiológico em policiais militares do Estado de São Paulo - Guida, Heraldo Lorena [UNESP] (2010)
INTRODUCTION: The military police are a population exposed to noise impact due to training with firearms. OBJECTIVE: To investigate the audiological profile of the military police in São Paulo state, and to correlate the age and duration of exposure and audiological findings. METHOD: In this study of case series, cross-sectional audiological evaluation was performed in 200 police officers being 169 (84.5%) were male and 31 (15.5%) females, aged between 25 and 45 years (mean 38.83 ± 5.05), average service time of 16.80 ± 6.27 years. RESULTS: The main complains were: tinnitus (n=52/26%), hearing loss (n=36/18%), ear fullness (n=24/12%) and autophonia (n=24/12%). Impedance were found in 100% of type A curves (JERGER, 1970), and recruitment was present in 20 (10%) cases. According to the results of audiometry, the data showed that 54 (27%) right ears and 56 (28%) left ears had hearing loss. The degree of loss with higher prevalence was 1 and 2 (MERLUZZI et al., 1979), 85 (42.5%) cases. There was significant correlation between age and exposure time with the worsening of audiometric thresholds in both ears. CONCLUSION: From the audiological data analysis was possible that the military police are a population that presents a risk to develop hearing loss. Thus, we see the need for implementation of hearing conservation program for the military police.